How Reliable Are Hematological Parameters in Predicting Uncomplicated Plasmodium falciparum Malaria in an Endemic Region?. (2nd June 2013) - Muwonge, Haruna; Kikomeko, Sharif; Sembajjwe, Larry Fred; Seguya, Abdul; Namugwanya, Christine
Abstract : Background . Malaria remains endemic in Sub-Saharan Africa. Hematological changes that occur have been suggested as potential predictors of malaria. This study was aimed at evaluating the diagnostic relevance of hematological parameters in predicting malaria. Methods . A cross-sectional study involving 370 patients with signs and symptoms of malaria was conducted at Mulago Hospital, Kampala, from May, 2012 to February, 2013. Thin and thick blood films were prepared for each patient and stained with Giemsa to aid the detection of malaria parasites. Patients' hematological parameters were determined. Results . Out of the 370 patients, 61 (16.5%) had malaria. Significant differences in the hematological parameters between P. falciparum malaria parasitemic patients and nonparasitemic patients were only observed in mean (±SD) of the differential monocyte count (10.89 ± 6.23% versus 8.98 ± 5.02%, P = 0.01 ) and the platelet count (172.43 (± 80.41)× 10 3 cells/µl versus 217.82 ± (95.96)× 10 3 cells/µlP = 0.00 ). The mean (±SD) values of the red blood cell indices (hemoglobin count, MCV, MCH, and MCHC), the differential neutrophil and lymphocyte counts, and the mean platelet volume (MPV) did not significantly differ between the two groups. Conclusion . Hematological changes are unreliable laboratory indicators of malaria in acute uncomplicated Plasmodium falciparum malaria.